Penggugatan Kasus Wanprestasi Investasi Hotel dan Apartemen Milik Yusuf Mansur - Apriliana Dwi Harwanti; Adisty Aulia Rosadi; Rania Syifa Busroni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In an agreement, there is often a situation where one party fails to fulfill its obligations as previously agreed upon in the contract, resulting in an occurrence commonly known as a breach of contract. As regulated in Article 1243 of KUHPerdata, the occurrence of a breach of contract can lead to claims for compensation. This research discusses a case study on the position of breach of contract in the investment of apartments and hotels by Yusuf Mansur, as well as the resolution of the case. The research method used in this article is a qualitative approach and literature review. The case has been resolved through litigation by filing a breach of contract lawsuit in the Pengadilan Negeri Tangerang.